THE INFLUENCE OF SECURITY, E-SERVICE QUALITY, AND BRAND IMAGE ON PURCHASING DECISIONS IN BLIBLI E-COMMERCE - Martin; Mangasi Butar Butar; Hannah; Melisa Marsel; Robinhot Gultom (Mount Hope Economic Global Journal, 2025)
This study aims to test and analyze the effect of security, e-service quality, and brand image on purchasing decisions. In the data of the largest e-commerce in Indonesia, Blibli ranks fourth with 337.4 million visits in 2023. In terms of consumer visits, Blibli is still inferior to several other competitors. This shows that Blibli has not been able to fully obtain a dominant purchasing decision compared to other competitors. In purchasing decisions, there are many factors that are taken into consideration in purchasing decisions, the first of which is convenience. The convenience factor is important because the use of communication tools is a way for consumers to believe that by using a certain system they will be error-free. The next factor is security, security is valued as the ability of online stores to control and maintain the security of data transactions. In the decision to purchase a product, the image of the product to be purchased can influence consumers' desire to buy the product. The better the product image, the more interested consumers will be in the product. This study uses quantitative research with the sample used was 97 respondents from the Faculty of Law, Prima Indonesia University. The data analysis method uses multiple linear regression. Convenience sampling was used as the sampling method. The conclusion of this study is that security, e-service quality, and brand image have a significant effect, both simultaneously and partially on purchasing decisions at Blibli for students of the Faculty of Law, Prima Indonesia University